Planetesimal formation during protoplanetary disk buildup - Drążkowska, Joanna; Dullemond, Cornelis (Astronomy and astrophysics, 2018)
Context. Models of dust coagulation and subsequent planetesimal formation are usually computed on the backdrop of an already fully formed protoplanetary disk model. At the same time, observational studies suggest that planetesimal formation should start early, possibly even before the protoplanetary disk is fully formed.Aims. In this paper we investigate under which conditions planetesimals already form during the disk buildup stage, in which gas and dust fall onto the disk from its parent molecular cloud.Methods. We couple our earlier planetesimal formation model at the water snow line to a simple model of disk formation and evolution.Results. We find that under most conditions planetesimals only form after the buildup stage, when the disk becomes less massive and less hot. However, there are parameters for which planetesimals already form during the disk buildup. This occurs when the viscosity driving the disk evolution is intermediate (αv ~ 10−3−10−2) while the turbulent mixing of the dust is reduced compared to that (αt ≲ 10−4), and with the assumption that the water vapor is vertically well-mixed with the gas. Such a αt ≪ αv scenario could be expected for layered accretion, where the gas flow is mostly driven by the active surface layers, while the midplane layers, where most of the dust resides, are quiescent.Conclusions. In the standard picture where protoplanetary disk accretion is driven by global turbulence, we find that no planetesimals form during the disk buildup stage. Planetesimal formation during the buildup stage is only possible in scenarios in which pebbles reside in a quiescent midplane while the gas and water vapor are diffused at a higher rate.